Synthesis of a porphyrin with histidine-like chelate: an efficient path towards molecular PDT/SPECT theranostics. Issue 75 (19th August 2020) - Yap, Steven Y.; Savoie, Huguette; Renard, Isaline; Burke, Benjamin P.; Sample, Harry C.; Michue-Seijas, Saul; Archibald, Stephen J.; Boyle, Ross W.; Stasiuk, Graeme J.
Abstract : "Click" chemistry was utilised to synthesis multifunctional theranostic drugs with therapeutic, diagnostic, and prostate-cancer targeting capabilities, paving a path towards "personalised" medicine ultimately improving patients' quality of life. Abstract : The goal of "personalised" medicine has seen a growing interest in the development of theranostic agents. Bifunctional, and targeted-trifunctional, theranostic water-soluble porphyrins with a histidine-like chelating group have been synthesised via copper-catalysed azide–alkyne cycloaddition (CuAAC) "click" chemistry in high yield and purity. They are capable of photodynamic treatment and [ 99m Tc(CO)3 ] + complexation for single-photon emission computed tomography (SPECT) imaging, with a radiochemical yield of >95%. The toxicity and phototoxicity were evaluated on HT-29 cells, DU145, and DU145-PSMA cell lines, with the targeted theranostic showing more potent phototoxicity towards DU145-PSMA expressing cells.